Online Community Building in Distance Education: The Case of Social Presence in the Blackboard Discussion Board versus Multimodal VoiceThread Interaction - Julian Chen; Tatiana Bogachenko (Educational Technology & Society, 2022)
Establishment of online communities in distance education has been linked to improved engagement, retention, and learning outcomes. This study investigates how online community building was fostered in the text-based Discussion Board (DB) and multimodal VoiceThread (VT) in one of the postgraduate units offered by Open Universities Australia. Specifically, it delves into how social presence – encompassing affective, cohesive, and interactive indicators in the Community of Inquiry (CoI) – was facilitated on both platforms. Findings show that VT multimodal postings triggered more instances of social presence than DB postings across all three indicators. VT communication also bolstered a continuous and inclusive discourse by bringing participants closer by addressing members’ names and mentioning posts made by others. It is concluded that multimodality afforded by VT can be more advantageous for online collaboration and engagement. Suggestions for course design to establish stronger social presence and for evaluation of multimodal platforms are also offered.